Missionary Bishop : Jean-Marie Odin in Galveston and New Orleans - Foley, Patrick, 1933- (Book collections on Project MUSE., 2013)
In 1822, a young French missionary priest arrived in America, where he would devote the rest of his life to the mission field on behalf of the Catholic Church. Jean-Marie Odin served first in Missouri and Arkansas, then in 1840 moved to Texas, becoming the first Bishop of Galveston in 1847. He held that office until 1861, when he became Archbishop of New Orleans. The twenty years he served in Texas were important years in the life of the young republic-turned-state. His life and career during this period allow readers to view, in the words of this book's foreword, "French missionaries and their collaborators treading the almost limitless Texas landscape to serve encampments of settlers and to preach the Gospel in English, French, Spanish, and German." His decade in New Orleans during the Civil War and Reconstruction spans a period of immense importance to America, the region, and the Roman Catholic Church. Finally, in 1870, Odin returned to Hauteville, France, and died in the same home in which he had been raised. The role of the church in those turbulent times is revealed through the life and ministry of Jean-Marie Odin.